ORDINARY LEAST SQUARE ANALYSIS IN ESTIMATING THE PRODUCTION FACTORS OF MILKFISH (Chanos chanos) NURSERY CULTIVATION IN TURI DISTRICT, LAMONGAN - M. Khairul Anam; Rhochmad Wahyu Illahi; Rosidah Wahyu Ningtyas; Moh. Wazirul Haq (Universitas Mataram, 2024)
Milkfish is one of the freshwater fish commodities highly favored by the community, as evidenced by the increasing market demand annually. The demand for milkfish nursery continuously rises in line with the expansion of milkfish enlargement efforts for bait and consumption sizes. Therefore, intensive engineering of milkfish nursery production technology is necessary to fulfill the nursery demand both in quantity and quality. This research aims to understand milkfish cultivation practices with the nursery production system in Turi District, Lamongan Regency, and analyze the production factors influencing milkfish cultivation with the aforementioned system. This study employs a quantitative descriptive method. Data collected include both primary and secondary data, gathered through observation, interviews, questionnaires, and documentation techniques. The research findings indicate that factors positively affecting the income of milkfish farmers with the nursery production system include seed costs, fertilizer costs, and land area. This implies that the higher the utilization of these variables, the greater the income. On the other hand, labor costs and feed costs do not positively influence the income of milkfish farmers with the nursery production system.